On the controllers' design to stabilize ground resonance helicopter - Ignácio da Silva, José A. [UNESP]; Bueno, Douglas D. [UNESP]; de Abreu, Gustavo L. C. M. [UNESP] (SAGE Publications, 2019)
Ground resonance (GR) in helicopters is a potentially catastrophic instability commonly caused by coalescence of the regressive cyclic blade lag mode with the fuselage motion in certain rotor speed ranges. It can limit the helicopter operational envelope and the design of this type of vehicle can become a difficult task. Although a broad class of actuators allows the use of active and semi-active techniques to design feedback-based control systems, a limited number of works in the literature introduce formulations to compute the controller gain to suppress this phenomenon. Also, commonly, a control approach defines a feedback, particularly to a specific rotor speed. In this context, this work introduces an alternative methodology to design an active control system to stabilize GR of a helicopter. The proposed approach can suppress this instability in all rotor speed ranges by using only one control gain. Two strategies are proposed based on linear matrix inequalities (LMIs). The Lyapunov stability criteria are used and the unstable rotor speed is considered as an uncertain parameter to define an associated convex space. Using convex optimization, a robust control gain is computed until all the unstable rotor speed range is stabilized. Numerical simulations are carried out to demonstrate the effectiveness of this methodology. The results confirm the viability of the proposed approach to design active and semi-active controllers.
Keywords: controller design; Ground resonance helicopter; linear matrix inequalities; robust control gain; rotor speed range stabilization